Modifiable pathways for colorectal cancer: a mendelian randomisation analysis. (January 2020) - Cornish, Alex J; Law, Philip J; Timofeeva, Maria; Palin, Kimmo; Farrington, Susan M; Palles, Claire; Jenkins, Mark A; Casey, Graham; Brenner, Hermann; Chang-Claude, Jenny; Hoffmeister, Michael; Kirac, Iva; et al.
Summary: Background: Epidemiological studies have linked lifestyle, cardiometabolic, reproductive, developmental, and inflammatory factors to the risk of colorectal cancer. However, which specific factors affect risk and the strength of these effects are unknown. We aimed to examine the relationship between potentially modifiable risk factors and colorectal cancer. Methods: We used a random-effects model to examine the relationship between 39 potentially modifiable risk factors and colorectal cancer in 26 397 patients with colorectal cancer and 41 481 controls (ie, people without colorectal cancer). These population data came from a genome-wide association study of people of European ancestry, which was amended to exclude UK BioBank data. In the model, we used genetic variants as instruments via two-sample mendelian randomisation to limit bias from confounding and reverse causation. We calculated odds ratios per genetically predicted SD unit increase in each putative risk factor (ORSD ) for colorectal cancer risk. We did mendelian randomisation Egger regressions to identify evidence of potential violations of mendelian randomisation assumptions. A Bonferroni-corrected threshold of p=1·3 × 10 −3 was considered significant, and p values less than 0·05 were considered to be suggestive of an association. Findings: No putative risk factors were significantly associated with colorectal cancer risk after correction for multiple testing. However, suggestive associations with increased risk were noted for genetically predicted body fat percentage (ORSD 1·14 [95% CI 1·03–1·25]; p=0·0086), body-mass index (1·09 [1·01–1·17]; p=0·023), waist circumference (1·13 [1·02–1·26]; p=0·018), basal metabolic rate (1·10 [1·03–1·18]; p=0·0079), and concentrations of LDL cholesterol (1·14 [1·04–1·25]; p=0·0056), total cholesterol (1·09 [1·01–1·18]; p=0·025), circulating serum iron (1·17 [1·00–1·36]; p=0·049), and serum vitamin B12 (1·21 [1·04–1·42]; p=0·016), although potential pleiotropy among genetic variants used as instruments for vitamin B12 constrains the finding. A suggestive association was also noted between adult height and increased risk of colorectal cancer (ORSD 1·04 [95% CI 1·00–1·08]; p=0·032). Low blood selenium concentration had a suggestive association with decreased risk of colorectal cancer (ORSD 0·85 [95% CI 0·75–0·96]; p=0·0078) based on a single variant, as did plasma concentrations of interleukin-6 receptor subunit α (also based on a single variant; 0·98 [0·96–1·00]; p=0·035). Risk of colorectal cancer was not associated with any sex hormone or reproductive factor, serum calcium, or circulating 25-hydroxyvitamin D concentrations. Interpretation: This analysis identified several modifiable targets for primary prevention of colorectal cancer, including lifestyle, obesity, and cardiometabolic factors, that should inform public health policy. Funding: Cancer Research UK, UK Medical Research Council Human Genetics Unit Centre, DJ Fielding Medical Research Trust, EU COST Action, and the US National Cancer Institute.